Role of copper in improving the seed quality of sunflower (Helianthus annuus) - NAUTIYAL, N; SHARMA, C P; CHATTERJEE, C (The Indian Journal of Agricultural Sciences, 2013)
'Morden' sunflower (Helianthus annuus L.) was grown in refined sand at a copper supply ranging from acutedeficiency (0.00065 mg/litre) to excess (6.5 mg/litre) to study the effect of variable copper on growth, biomass,oilyield,etc. The oil content in seeds was highest at 0.065 mg Cu/litre and compared to this, it decreased more indeficiency (